2020
DOI: 10.3389/fsurg.2020.596925
|View full text |Cite
|
Sign up to set email alerts
|

Current Novel Advances in Bronchoscopy

Abstract: Screening for lung cancer has changed substantially in the past decade since The National Lung Screening Trial. The resultant increased discovery of incidental pulmonary nodules has led to a growth in the number of lesions requiring tissue diagnosis. Bronchoscopy is one main modality used to sample lesions, but peripheral lesions remain challenging for bronchoscopic biopsy. Alternatives have included transthoracic biopsy or operative biopsy, which are more invasive and have a higher morbidity than bronchoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…Combined with the characteristics of the lesions, the radial ultrasonic localization images of PPNs can be divided into the following 3 types: concentric, eccentric, and adjacent (10). VNB is a method for forming a 3D, virtual bronchial tree image, which is generated by importing chest CT data into a special system, and can guide the bronchoscope to the peripheral lung target lesions (14). Gupta et al reported that the diagnostic yield of rEBUS-TBLB for PPN was about 60-70%, but when used in combination with VBN, the diagnostic yield reached 63.3-84% (15).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the characteristics of the lesions, the radial ultrasonic localization images of PPNs can be divided into the following 3 types: concentric, eccentric, and adjacent (10). VNB is a method for forming a 3D, virtual bronchial tree image, which is generated by importing chest CT data into a special system, and can guide the bronchoscope to the peripheral lung target lesions (14). Gupta et al reported that the diagnostic yield of rEBUS-TBLB for PPN was about 60-70%, but when used in combination with VBN, the diagnostic yield reached 63.3-84% (15).…”
Section: Discussionmentioning
confidence: 99%
“…Nội soi phế quản đã phát triển mạnh trong vài thập kỷ qua và được sử dụng rộng rãi trong chẩn đoán và điều trị các bệnh hô hấp. Với sự phát triển của các kỹ thuật nội soi phế quản mới như nội phế quản siêu âm, nội soi phế quản siêu nhỏ, nội soi phế quản có hướng dẫn từ trường… đã mở rộng phạm vi chẩn đoán bệnh phổi [1,2]. Nội soi phế quản can thiệp (nội soi điều trị) đã phát triển nhanh chóng từ những năm 2000.…”
Section: đặT Vấn đềunclassified
“…We believe a multidisciplinary approach including interventional pulmonologists and thoracic surgeons is crucial to optimize the workup of this group of patients and expedite more invasive diagnostic approaches or therapeutic interventions when needed. -SPiN Perc™ 70-80 12,13 17-21 12,13 Monarch™ 69-77 21,23,24 3.6 23,24 Intuitive Ion™ 79 20,32 0 20,32…”
Section: Other Navigation Platforms and New Technologymentioning
confidence: 99%